Effectiveness of a Trauma-Informed Care Initiative in a State Child Welfare System: A Randomized Study. (February 2019) - Jankowski, M. Kay; Schifferdecker, Karen E.; Butcher, Rebecca L.; Foster-Johnson, Lynn; Barnett, Erin R.
Trauma-informed care (TIC) initiatives in state child welfare agencies are receiving more attention, but little empirical evidence exists as to their efficacy. The purpose of this study was to assess changes in self-reported practices and perceptions of child welfare staff involved in a multifaceted, statewide TIC intervention. Ten child welfare offices were matched and randomized to an early or delayed cohort. Staff were surveyed at Time 1 prior to any intervention, Time 2 postintervention for Cohort 1, and Time 3 postintervention for Cohort 2. The survey covered six domains: trauma screening, case planning, mental health and family involvement, progress monitoring, collaboration, and perceptions of the state's overall system performance. Linear mixed modeling assessed the effect of the intervention. Cohort by time interaction was significant for three intervention targets. We demonstrate, using a rigorous study design, the mixed results of a multimodal intervention to improve trauma-informed attitudes, practices, and system performance. TIC initiatives must account for complex, dynamic contextual factors.